2014
DOI: 10.1007/s00234-014-1355-x
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal wall enhancement and perianeurysmal edema after endovascular treatment of unruptured cerebral aneurysms

Abstract: Our study demonstrates the prevalence and some appreciation of the natural history of aneurysmal wall enhancement and perianeurysmal brain edema following endovascular treatment of unruptured aneurysms. Aneurysmal wall enhancement is a common phenomenon while perianeurysmal edema is rare. These phenomena are likely related to the presence of inflammatory reaction near the aneurysmal wall. Both phenomena are usually asymptomatic and self-limited, and prophylactic treatment is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Of the two large case series, Su et al 4 reported no statistical significance between aneurysm size and the development of PAVO in their 132 cases of 8–16 mm in size (mean 12.1 mm), whereas Lukic et al 5 report a statistically significant but clinically insignificant OR for increasing aneurysm volume and PAVO, p<0.05, OR 1.010 (95% CI 1.006 to 1.015).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Of the two large case series, Su et al 4 reported no statistical significance between aneurysm size and the development of PAVO in their 132 cases of 8–16 mm in size (mean 12.1 mm), whereas Lukic et al 5 report a statistically significant but clinically insignificant OR for increasing aneurysm volume and PAVO, p<0.05, OR 1.010 (95% CI 1.006 to 1.015).…”
Section: Discussionmentioning
confidence: 97%
“…The inflammatory reaction, responsible for the production of thrombus postcoiling, is hypothesised to affect the adjacent blood–brain barrier if the aneurysm wall is embedded within the brain parenchyma 4. Vasogenic oedema occurs from an increase in permeability following the disruption of the blood–brain barrier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have examined IVWM findings after endovascular treatment of IAs. Using standard MRI sequences, it has been identified that IA wall enhancement is common, occurring in 19-66 % of patients treated with endovascular coiling or flow-diversion stents [61][62][63]. Procedural factors, such as the density of coil packing or coil material and IA-specific characteristics, such as IA size or location, influenced the incidence of wall enhancement, but the MRI findings did not predict IA occlusion success, procedural complications, or post-procedure morbidity such as IA rupture.…”
Section: Introductionmentioning
confidence: 99%